2022
DOI: 10.1021/acs.jafc.2c01905
|View full text |Cite
|
Sign up to set email alerts
|

Wild Jujube (Ziziphus jujuba var. spinosa): A Review of Its Phytonutrients, Health Benefits, Metabolism, and Applications

Abstract: Wild jujube, Ziziphus jujuba Mill. var. spinosa (Bunge) Hu ex H. F. Chou, as a food and health supplement worldwide, has rich nutritional value. It contains nutrients such as nucleosides, amino acids, polysaccharides, and fatty oils. The fruits, seeds, and leaves of wild jujube can all be used for food, medicine, or health care purposes. Among these, the fruits play many roles, such as antioxidant, antibacterial, and anti-inflammatory functions, and can be used as a natural nutritional supplement to prevent ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 118 publications
1
24
0
Order By: Relevance
“…To explore the substrate specificity of ZjOGT3, 34 flavonoids were screened by enzymatic assay using UDP-Glc as sugar donor (Figure 2). These substrates included 7,4 -dihydroxy flavones (1-9), 7,4 -dihydroxy flavanones (10-11), 3-O-glycosylated 7,4 -dihydroxy flavones (12)(13)(14)(15)(16)(17), 7 or 4 monohydroxy flavones (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), isoflavones (29-31), isoflavans (32), isoflavone glycoside (33), and chalone (34). LC/MS analysis revealed that ZjOGT3 could catalyse glucosylation of all the 34 substrates.…”
Section: Substrate Promiscuity and Synthetic Applicability Of Zjogt3mentioning
confidence: 99%
See 2 more Smart Citations
“…To explore the substrate specificity of ZjOGT3, 34 flavonoids were screened by enzymatic assay using UDP-Glc as sugar donor (Figure 2). These substrates included 7,4 -dihydroxy flavones (1-9), 7,4 -dihydroxy flavanones (10-11), 3-O-glycosylated 7,4 -dihydroxy flavones (12)(13)(14)(15)(16)(17), 7 or 4 monohydroxy flavones (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28), isoflavones (29-31), isoflavans (32), isoflavone glycoside (33), and chalone (34). LC/MS analysis revealed that ZjOGT3 could catalyse glucosylation of all the 34 substrates.…”
Section: Substrate Promiscuity and Synthetic Applicability Of Zjogt3mentioning
confidence: 99%
“…spinosa, Rhamnaceae family) is a medicinal plant native to China. Its seeds are used as the traditional Chinese medicine Suan-Zao-Ren for a long history to treat anxiety and depression 19 . This plant contains abundant flavonoid 4 -O-glycosides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to pharmacological investigations, jujube has various medical qualities, such as anti-obesity, anticancer, anti-inflammatory and antioxidant, as well as immunostimulating, gastrointestinal protective, and hepatoprotective properties. It also inhibits the production of foam cells in macrophages [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The codon preference of this experiment, different from most codon usage preferences in dicots, is one of the plants that ends with G/C. At present, research on ZSS mainly focuses on the chemical composition, modern pharmacological effects, mechanism of ZSS, and its preparations(Hua et al 2022;Ji et al 2017;Wang et al 2020…”
mentioning
confidence: 99%